Strategi Pemerintah Kota Manado Dalam Meningkatkan Pendapatan Asli Daerah Melalui Pajak Perhotelan - Jackson Boda; Elfie Mingkid; Antonius Purwanto (Sam Ratulangi University, 2022)
This research aims to: 1) knowing, reviewing, analyzing Manado City Government's strategy in increasing Regional Original Revenue through hotel taxes, and 2) knowing, studying, analyzing what factors support and hinder Manado City Government in increasing Regional Original Revenue through hotel tax. The type of research used in this research is descriptive qualitative and the collection technique is by observation, interviews and documentation. The informants in this study were the Head of the Manado City Regional Revenue Agency, the Head of the Tax and Retribution Service Division of Manado City Regional Revenue Agency, and hotel taxpayers. The results of the study show that: 1) The strategies adopted by the Manado City Government in increasing PAD through hotel taxes are: (a) Aggressive in applying sanctions and penalties for hospitalitytaxes, (b) Aggressive in improving hotel tax services, (c) Aggressive in increasing communication and counseling on hotel taxes, and (d) Aggressive in increasing the supervision of hotel taxes. Inhibiting factors: (a) Low discipline, compliance of hotel taxpayers to pay taxes, (b) Low honesty, awareness of hotel taxpayers manipulating the amount of income turnover so that tax payments are low, (c) Limited quantity of human resources working and the ineffectiveness of the joint task force in carrying out their duties and responsibilities (d) Administrative sanctionssuch as fines, less effective closures, (e) Lack of supporting facilities 6) Unfavorable external conditions, the spread of the COVID-19 virus pandemic.